Analisis Penetapan Harga Jual pada PT Mega Indah Sari Timur - Mustahar, Lutfiah Amalia; Idris, Hariany; Samsinar, Samsinar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the pricing strategy at PT Mega Indah Sari Timur. The type of research used is qualitative descriptive. The sample used in this study includes data and information on sales prices from 2021 to 2023 at PT Mega Indah Sari Timur. The data collection required includes sales price data and supporting evidence, conducting interviews with one of the staff members, noting the elements of sales prices and others during the interview, and processing the interview results obtained. The data analysis technique uses qualitative descriptive analysis. The results of the analysis show that the selling price method at PT Mega Indah Sari Timur is concluded. Based on the research findings, there is a difference between the selling price applied by the company and the author using the markup method, specifically for the sun power granite 60 x 60 and the DKS consignment hardware (Dekson) htrd 0.3 in 2021, 2022, and 2023, where the company experiences annual price increases that do not align with the markup.